2020
DOI: 10.1177/1045389x20969836
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the elasticity of the melt and electrical conductivity of the solid of PP-HDPE copolymer CNT composites obtained by direct compounding versus dilution of a PP masterbatch

Abstract: Composites of multiwall carbon nanotubes (CNT) at 1, 2, and 3 wt.% on a polypropylene–polyethylene random copolymer matrix were prepared by melt compounding CNT powder and by dilution of a commercial polypropylene masterbatch (PMB). While the shear viscosity shows similar behavior for both dilution modes, the differences in their elastic properties clearly show the effect of the addition method and the presence of the PMB. This also indicates the relevance of having a difficult to mix masterbatch to enhance th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…A schematic illustration is presented in Figure 7 . In addition, the percolation threshold of the MWCNTs (Nanocyl NC7000) was reported to be around 2 wt.% [ 41 ]. In the 4.5% GNP/1.5% CNT–PVDF composition, the content of the MWCNTs was just before the percolation occurred.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A schematic illustration is presented in Figure 7 . In addition, the percolation threshold of the MWCNTs (Nanocyl NC7000) was reported to be around 2 wt.% [ 41 ]. In the 4.5% GNP/1.5% CNT–PVDF composition, the content of the MWCNTs was just before the percolation occurred.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers reported [ 43 ] that amorphous regions in semi-crystalline polymers tend to have higher thermal expansion than do crystalline regions. Thus, the lowest crystallinity of the 4.5% GNP–1.5% CNT–PVDF composite ( Table 3 ), compared to the neat PVDF and the other nanocomposites, confirmed the highest sensitivity to thermal expansion of this hybrid composite, which may provoke the disruption of the weak percolated structure of MWCNTs around the percolation threshold, that is, 1–2 wt.% for the extrusion-processed polymer composites [ 28 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported the mechanical and electrical properties of nanocomposites containing CNT. For example, the addition of 1, 2 and 3 wt.% of CNT by melt compounding with a polypropylene (PP) copolymer through the dilution of a masterbatch containing 20 wt.% of CNT, and the comparison with direct compounding of 1, 2 and 3 wt.% CNT into PP, was investigated [29] . An increase in electrical conductivity was obtained by both methods, however due to poorer dispersion of CNT achieved by masterbatch dilution, these composites showed comparitively lower conductivity than those produced by direct CNT compounding into the PP matrix.…”
Section: Introductionmentioning
confidence: 99%